2020
DOI: 10.3390/educsci10030051
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Mind-Wandering from Eye Movement and Oculomotor Data during Learning Video Lecture

Abstract: The purpose of this study was to detect mind-wandering experienced by pre-service teachers during a video learning lecture on physics. The lecture was videotaped and consisted of a live lecture in a classroom. The lecture was about Gauss's law on physics. We investigated whether oculomotor data and eye movements could be used as a marker to indicate the learner’s mind-wandering. Each data was collected in a study in which 24 pre-service teachers (16 females and 8 males) reported mind-wandering experience throu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In one study involving a reading task, eye movements became slower or less frequent during a period prior to a participant's report of mind-wandering compared with a period prior to reporting of being on-task (concentrating) (Uzzaman & Joordens, 2011). Another study reported that the saccade frequency was lower and the fixation dispersion was more limited in mind-wandering states than in attentive states during video lectures (Jang et al, 2020). Therefore, compared with the task phase, people are likely to be in a mind-wandering state in the after-task phase because no specific goal is given.…”
Section: Introductionmentioning
confidence: 99%
“…In one study involving a reading task, eye movements became slower or less frequent during a period prior to a participant's report of mind-wandering compared with a period prior to reporting of being on-task (concentrating) (Uzzaman & Joordens, 2011). Another study reported that the saccade frequency was lower and the fixation dispersion was more limited in mind-wandering states than in attentive states during video lectures (Jang et al, 2020). Therefore, compared with the task phase, people are likely to be in a mind-wandering state in the after-task phase because no specific goal is given.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Wang et al ( 2020b ) Fixation dispersion Dispersion on the screen divided by the maximum dispersion. 3 Jang et al ( 2020 ) …”
Section: Resultsmentioning
confidence: 99%
“…While an increase in fixation count may imply that an AOI is prominent (Kokoç et al, 2020 ), the same metric can also represent a higher level of difficulty when processing an AOI (Wang et al, 2019b ). A longer fixation duration on an AOI can evince the investment of more cognitive resources (Pi et al, 2020a ), but it can also be used to approximate mind-wandering (Jang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The restricted field of view displayed on the screen during microscopic ear surgery, slows down gaze exploration, leading to a reduced perception of the middle ear anatomy. Moreover, several authors reported long average fixation duration to be an indicator of either a participant’s difficulty extracting information from a display or mind wandering (21–24). Long and steady fixations increase visual fatigue leading to higher perceived discomfort during video observation (25,26).…”
Section: Discussionmentioning
confidence: 99%